The politics of military procurement: the F-35 purchasing process in Canada and Australia Compared - Howlett, Alexander; Migone, Andrea Riccardo; Howlett, Michael (Defence studies, 2023)
The willingness of defence departments to select the F-35 Joint Strike Fighter (JSF) for their fifth-generation multirole fighter has frequently been analyzed as stemming from the close historical connections allies such as Japan or Canada have with the United States. However, such an approach glosses over or ignores the operation of military procurement processes which are more idiosyncratic and subject to many pushes and pulls from different actors and directions. This article compares the experiences of Australia and Canada in procuring the JSF. Both countries are British Commonwealth members, with a long history of supporting western, and in particular, US alliances. But while Australia has secured its F-35 procurement and the Royal Australian Air Force (RAAF) has already received its F-35s, Canada has only recently overcome a lengthy F-35 procurement battle that remains mired in controversy and will not deliver to the Royal Canadian Air Force (RCAF) an aircraft for several years yet. This comparative case study between Australian and Canadian defence priorities offers a new explanation for this disparity of procurement success based on the need to both create and maintain alignment between government strategic defence policy and military service doctrine if major platform purchasing decisions are to survive.